Use of Magnesium Sulphate in the Management of Severe Preeclampsia at the Centre University Hospital of Mother and Child (CHU-MEL) Cotonou Benin.... - TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; LOKOSSOU, Mègnissè Sèna H. S.; ABOUBAKAR, MOUFALILOU; HOUNKPATIN, BENJAMIN IGNACE B.; PERRIN, RENÉ-XAVIER (My University, 2017)
Objectives: To evaluate professionals practices and the contribution of magnesium sulphate in a better medical care for persons with severe preeclampsia at CHU-MEL. Materials and Method: We conducted a retrospective and cross-sectional study with the aim come up with a descriptive and analytical paper. Our study was conducted from January 15th, 2015 to July 15th, 2016, i.e. during eighteen (18) months. The sampling was exhaustive. The population was made of all patients admitted for severe preeclampsia with or without complications. Confidentiality requirements were met and informed consent obtained from all subjects. For the analytical study, the chi-square test was used and the difference was statistically significant with a p-value inferior than 0.05. Results: The prevalence of preeclampsia during the study period was 7.70% (447/5805 deliveries). Out of the 312 files that we were able to find and exploit, 272 revealed that patients were administrated a dose of magnesium sulphate, at a frequency estimated at 87.18%. Irregularities were noted in the protocol implementation: the maintenance dose was administered in 30% of cases, as a slow infusion (66.33%), for less than 24 hours in 37.24% of cases, and under supervision only in 22.62% of cases. Primary and secondary prevention of eclampsia was achieved in 98.5% and 80% of cases, respectively. Respecting the duration of treatment significantly reduces the onset and recurrence of seizures (p=0.003 and p=0.004). Decreased reflexes and respiratory distress were noted in 34.78% and in 8.7% of cases respectively. The maternal lethality rate was 1.34% and the stillbirth rate was 11.40%. Conclusion: Magnesium sulphate intake is undeniable in dealing with severe preeclampsia, but this solution/ drug is misused at the CHU-MEL. Appropriate solutions must therefore be taken in the execution and monitoring of the protocol.
Keywords: Severe preeclampsia; Magnesium sulphate